Investigation Of Oscillatory Flow Inside Thermoacoustic System With Two Different Flow Frequencies - Allafi, Waleed Almukhtar Allafi (2020)
Thermoacoustic system is one of the alternative technologies that provides green working principles. Complex fluid flow and energy transfer interactions happen between an oscillatory flow and a solid material during the operation of thermoacoustic device. The understanding of the flow behaviour in the interior structure in oscillating environments are one of the keys to a better design and development of the system. This study represents fluid dynamics investigation of an oscillatory flow across a parallel-plates structure inside a standing wave theormoacoustic system by using a two-dimensional ANSYS FLUENT CFD (computational fluid dynamics) of SST k-ω turbulence model. The boundary conditions of CFD model, the experimental work procedure and the validation of the model with the experimental data and theoretical solution were explained in detail. Two different operating frequencies of 14.2 Hz and 23.6 Hz were investigated. The results showed that there are several significant findings that can be highlighted based on vortex shedding pattern and entrance region investigation. Instability of vortex structures at the end of the plates were observed at low amplitude for all drive ratio cases for both frequencies. Two layers (main vortex boundary layer and secondary vortex boundary layer) were detected on each surfaces of the plate in both investigated flow frequencies. A weak vortex layer was observed to appear inside the channel near to the surface of the plates at low amplitude in the first two phases of oscillatory flow starting from 0.65% drive ratio up to the maximum drive ratio of 3% for low frequency of 14.2 Hz. For high frequency of 23.6 Hz, this weak area appeared at the second and the third phases starting from 0.83% drive ratio up to the maximum drive ratio. The secondary layer for high frequency appeared stronger than that at low frequency. The results showed that the main vortex structure was always attached to the plate for both flow frequencies. At low frequency, the maximum extension of vortex is normally detected at phase Ф8. At high flow frequency, the maximum extension of vortex happens at a later phase of Ф10. For the entrance region investigation, the axial velocity profiles at low amplitude at the first phase of oscillatory flow (for both flow directions) were significantly affected by the impinging flow for both flow frequencies. Slug velocity profile shape was detected exactly at the ends of the channel for low frequency when the flow decelerates. Two regions (entrance region and exit region) were detected at the ends of the channel for both frequencies. Entrance region for 14.2 Hz frequency extends to longer distance into the channel compared to 23.6 Hz. For both frequencies the influence of the entrance region was increasing as drive ratio increases and when the amplitude increases in each drive ratio. The fluctuation of the exit region at low drive ratio for 14.2 Hz frequency was less than that for high frequency. The exit region almost disappeared as flow amplitude increases to high drive ratios. These results are expected to contribute towards better understanding of fluid dynamic behaviour that will influence performance of a real thermoacoustic system.